Evolusi Biologis dan Ancaman Kepunahan Manusia: Mempertemukan George L. Murphy dengan Film-Trilogi Planet of The Apes tentang Isu-Isu Kosmologi, Evolusi, dan Bioteknologi - Arulangi, Ronald (Faculty of Theology Duta Wacana Christian University, 2020)
AbstractThis article discusses George L. Murphyâ€™s argument that the development of science and technology in the early 21st Century challenges the relevance of core religious theories including theology of nature, theidea of the loving God, and humanitarian ethics. He proposes a theology of the Cross of Jesus Christ as a lens for responding to that challenge. Here Murphyâ€™s theological perspective is put in dialogue with a perspective that departs from the trilogy films: â€œRise of the Planet of the Apesâ€, â€œDawn of the Planet of the Apesâ€, and â€œWar for the Planet of Apes.â€ Employing Revised Correlational method, this article suggests a more optimistictheological reflection concerning cosmology, evolution, biotechnology, the future of humankind, and harmony. AbstrakArtikel ini membahas argumen George L. Murphy yang menilai perkembangan sains dan teknologi di awal abad ke-21 menggugat relevansi dari teori-teori keagamaan yang inti, termasuk teologi tentang alam, gagasan tentang Tuhan yang pengasih, dan etika humanitarian. Murphy mengusulkan persepektif teologi Salib Yesus Kristus sebagai lensa untuk merespon gugatan tersebut. Dalam artikel ini, pandangan Murphy didialogkandengan pandangan yang ditarik dari trilogy film â€œRise of the Planet of the Apesâ€, â€œDawn of the Planet of the Apesâ€, dan â€œWar for the Planet of Apesâ€. Menggunakan metode Korelasional yang Diperbarui, studi ini menghasilkan refleksi etis-teologis yang optimisik tentang kosmologi, evolusi, bioteknologi, masa depanmanusia, dan harmoni.